REPRODUCTIVE BIOLOGY OF POKEA CLAM Batissa violacea var. celebensis, VON MARTENS 1897 AT LASOLO ESTUARY, SOUTHEAST SULAWESI - . Bahtiar (Department of Marine Science and Technology, Faculty of Fisheries and Marine Science, IPB University, 2017)
Pokea clam Batissa violacea var. celebensis von Martens 1897 that inhabits the substrates of some estuaries in Southeast Sulawesi has a tendency to have different reproductive pattern. The aim of this study was to determine the sex ratio, gonadal maturity stage (TKG), gonadal maturity index (IKG) and the size at first gonad maturity of pokea in Lasolo estuary, Southeast Sulawesi. Samples were randomly collected using a traditional fishing gear called tangge. Sex ratio, TKG, IKG, and the size at first gonad maturity were determined using standard methods and formulas and then analyzed using Chi Square, quantitative description and non-linear regression. The results showed that the number of males were higher than the numbers of females, ranging from 71.85-89.84% and 10.16-28.15%, respectively. Gonadal maturity development of male and female occured simultaneously. Early gonadal maturity stage began in January. Spawning occurs twice, beginning with maturity in April and spawning in May and then again maturity in July and spawning in July until October. IKG values of male and female were relatively the same ranging from 2.56-31.92. The males matured earlier than the females at size 1.95 cm and 2.15 cm, respectively. Keywords: female, gonad, male, clam, maturity, spawning